Оцінка інвестиційної привабливості молочної галузі - Жорник, Тетяна Петрівна (НТУ "ХПІ", 2016)
Досліджені основні методичні підходи до оцінки інвестиційної привабливості на макрорівні економіки. Вивчені їх переваги та недоліки та запропонований комплексний метод оцінки інвестиційної привабливості. За допомогою цього методу проведена оцінка інвестиційної привабливості на прикладі молочної галузі України. Одержані результати дозволили виявити зміну рівня інвестиційної привабливості галузі в обраному періоді часу. Зроблено висновки щодо можливостей подальшого використання цього методу.

Basic methodological approaches to evaluation of investment attractiveness were researched. Their advantages and disadvantages for defined and thoroughly studied. Considering them, a new complex method of evaluation of investment attractiveness was proposed. With a help of this method evaluation of investment attractiveness was performed. Diary industry of Ukraine served as an example. The received results allowed to clearly see the change in the level of investment attractiveness of studies industry in certain period of time. Conclusions about possibilities of further application of this method were made.
Evaluation of investment attractiveness of a diary industry
Keywords: рейтинговий метод; показник; комплексна система; комплексний метод оцінки; industry; rating method; complex system